Mobile emergency care service in Floriano, Piauí: a golden time regression analysis - Matos, Matheus Halex Ferreira de; Ribeiro, Emanuella Pereira; Sousa, Julia Maria de Jesus; Baldoino, Ana Christina de Sousa; Silva, Filipe Melo da; Santos , Fernando Rocha dos; Rodrigues, Jailson Alberto (Acta Scientiarum. Health Sciences, 2024)
To analyze the influence pattern of the defining variables that compose the Golden time developed by the Brazilian Mobile Emergency Care Service [Serviço de Atendimento Móvel de Urgência] (SAMU-192) in a municipality in Piauí. This is a documentary, descriptive study with a quantitative approach. A total of 337 medical records referring to the year 2018 were verified; data were collected at SAMU’s decentralized base. A sphericity test was performed to verify the possibility of generating a linear model through Mauchly’s test. Initially, an alpha below 0.46 was obtained, but the variables were negatively interfering in the model. After two more verifications, it was concluded that removing the variable did not influence the parsimony of the model. The generalized linear model showed statistical significance as to its fit (p-value<0.001) for the intercept and (p-value = 0.042) for the outcome variable – Golden time. It was possible to understand that SAMU is a viable action for first-aid efficiency and promptness, as well as for patient transport to appropriate reference services.